Gambaran Perencanaan Program Pengendalian Penyakit Tuberkulosis (TB) Paru di Puskesmas Sikumana Kota Kupang Tahun 2023 - Maria Vivianty Djawa; Serlie K.A. Littik; Rina Waty Sirait (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, often leading to illness, disability, and death. Sikumana Health Center, Kupang City, recorded the highest TB cases with 140 cases in 2023, indicating that the control program has not been fully effective. This study aimed to describe the planning of the TB control program at the health center in 2023. A qualitative approach was used through in-depth interviews and documentation, involving four informants. Data were analyzed through collection, reduction, presentation, and conclusion. The findings show that human resources in the TB clinic are still limited, causing service gaps when the person in charge is absent. Facilities and infrastructure are adequate, and the planning stages—preparation, situation analysis, problem formulation, and drafting of RUK and RPK—have been carried out properly. However, challenges such as wide service coverage and community stigma that TB is hereditary may hinder treatment. The output consists of RUK and RPK documents, and the health center needs to strengthen education and counseling to improve public knowledge about TB.